2005
DOI: 10.1111/j.1444-2906.2005.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine supplemented practical diet on growth performance and taurine contents in whole body and tissues of juvenile Japanese flounder Paralichthys olivaceus

Abstract: The effect of dietary taurine on juvenile Japanese flounder was determined by feeding three taurine-supplemented experimental diets (TAU) and a commercial diet (CD) to evaluate a practical diet for juvenile Japanese flounder. Juvenile Japanese flounder were reared on the three experimental diets supplemented with taurine at 0, 0.5, 1.0% and CD. These diets were fed to juvenile Japanese flounder of an initial mean body weight of 0.2 g for 6 weeks at 20∞C and the taurine contents of the whole body and tissues we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 21 publications
7
52
0
3
Order By: Relevance
“…Similar observations were made in other species such as dentex Dentex dentex, summer flounder Paralichthys dentatus, Japanese flounder Paralichthys olivaceus, and red sea bream Pagrus major (Chatzifotis et al, 2008;Enterria et al, 2011;Kim et al, 2005;Matsunari et al, 2008b). Additionally, methionine supplementation does not influence the taurine status in rainbow trout , and dietary supplementation of cysteine increased tissue cystathionine, but not tissue taurine in juvenile Japanese flounder (Park et al, 2002).Since methionine is the precursor of cysteine via cystathionine and cysteine is used in the synthesis of taurine, this suggests inadequate synthesis rather than inadequate substrate availability for synthesis.…”
Section: Introductionsupporting
confidence: 76%
“…Similar observations were made in other species such as dentex Dentex dentex, summer flounder Paralichthys dentatus, Japanese flounder Paralichthys olivaceus, and red sea bream Pagrus major (Chatzifotis et al, 2008;Enterria et al, 2011;Kim et al, 2005;Matsunari et al, 2008b). Additionally, methionine supplementation does not influence the taurine status in rainbow trout , and dietary supplementation of cysteine increased tissue cystathionine, but not tissue taurine in juvenile Japanese flounder (Park et al, 2002).Since methionine is the precursor of cysteine via cystathionine and cysteine is used in the synthesis of taurine, this suggests inadequate synthesis rather than inadequate substrate availability for synthesis.…”
Section: Introductionsupporting
confidence: 76%
“…In fish species, the capacity for taurine synthesis is species-specific, and in highly carnivorous species such as bluefin tuna Thunns thynus, yellowtail, Japanese flounder Paralichthys olivaceus, and red sea bream it is markedly low or negligible [13,14]. In addition, the taurine requirement of yellowtail [37] and Japanese flounder [38,39] juveniles fed FM-based diets is more than 10 mg/g diet and about 15 mg/g diet, respectively, and for juvenile red sea bream fed a casein-based diet, it is 5 mg/g diet [40]. It is reported that dietary taurine supplementation improved growth performance of glass eel Anguilla anguilla [41] fed casein-based diets, and of cobia Rachycentron canadum [42], European sea bass Dicentrarchus labrax [43], and common dentex Dentex dentex [44] fed diets where FM was partially replaced with alternative protein sources.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, in freshwater species a taurine requirement has been observed only in rainbow trout fed FM-free diets (Gaylord et al, 2006, though such taurine requirement is still controversial (Boonyoung et al, 2013). In some marine species the estimated taurine requirement is considerably high (Goto et al, 2001;Kim et al, 2005;Qi et al, 2012;Lim et al, 2013) and this may help explain why a taurine requirement has been established essentially in marine fish, even when fed FM-containing diets.…”
Section: Fishmeal Sparing In Aquafeedsmentioning
confidence: 99%